Keratin-Nylon 6 engineered microbeads for adsorption of Th (IV) ions from liquid effluents - Gore P.M.; Khurana L.; Dixit R.; Balasubramanian K. (My University, 2025)
The applicability of novel porous microbeads (average diameter of about 2.0 mm) of α-keratin engineered with Nylon 6, have been investigated for the adsorption of radioactive and non-biodegradable Th (IV) ions from the effluents. Thorium ion uptake on the intrinsically compatible adsorbent system was investigated using experimental analysis and kinetic studies. The developed system demonstrates maximum adsorption efficiency of 66.26% under ecologically optimal conditions i.e. pH = 7, with 1000 ppm initial Th (IV) concentration at 303 K for 120 min. The experimental results reveal that the adsorption kinetics study best fits with the Dubinin-Radushkevich isotherm model (R2 = 0.993) and Intra-particle diffusion kinetics model (R2 = 0.995). The kinetic models namely Pseudo-first order, Pseudo-second order, particle diffusion, & Elovich were used for the adsorption study, and were compared and calculated using linear & nonlinear regression methods thermodynamic analysis revealed the spontaneity, viability and exothermic nature of the adsorption process with free energy change (ΔG0) of -11.48 kJ/mol. Further, the inter-polymer miscibility and compatibility was explored by atomistic molecular modelling and extended Flory-Huggins theory via Materials Studio software on geometrically minimized repeat units of Cysteine (functional group of α-keratin) and Nylon 6, employing Discover, Amorphous Cell, Forcite and Blends modules, which showed results to be consistent with FT-IR studies, revealing strong hydrogen bonding. © 2017 Elsevier Ltd. All rights reserved.